The new woman in print and pictures an annotated bibliography - Woods, Marianne Berger, 1941- (McFarland & Co., 2009)
"This annotated bibliography includes all period novels with a New Woman protagonist and all period articles with the New Woman as primary subject, along with several poems, cartoons, advertisements, and artworks. Because the New Woman was also the target of many derisive articles, poems, and visual works, these critical response pieces are included as well"--Provided by publisher.